Provincial Families of the Renaissance : Private and Public Life in the Veneto - Grubb, James S., 1952- (Book collections on Project MUSE., 1996)
Based on memoirs and other records left by thirteen merchant families from the Veneto cities of Verona and Vincenza, Provincial families of the Renaissance is an engrossing study of daily lives that have until now been overlooked by scholars. Grubb examines the attitudes and experiences of families undistinguished in their modest means and local ambitions from the majority of their compatriots, uncovering a detailed historical landscape rich in social obligations, commercial activities, and religious beliefs.